La mer vagabonde du jeune commandeur de Prévost
In this paper we propose an analysis emphasizing the theme of the Sea at presence in one of the less known of Prévost’s novels entitled Mémoires pour servir à l’Histoire de Malte, ou Histoire de la jeunesse du Commandeur (1741). In this barbaric adventure novel, the sea constitutes, on one hand, the spatial frame for adventure and love and, on the other, the place for reflection, misfortune, suffering, sea battles, as well as for the narrating hero’s inner struggle, a Malta’s chevalier who falls in love with a beautiful young girl, however unworthy of him. Here we can verify the development of themes such as the drift and dissolution of the self, the storms of wandering and love masked by an effervescent Romanesque. In the end, however, the young commendator leaves his mistress, disfigured by smallpox, which emphasizes Prévost’s pessimistic conception of fatal love.